2010
DOI: 10.1016/j.reprotox.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and prevalidation of the in vitro AR CALUX method to test androgenic and antiandrogenic activity of compounds

Abstract: To date there are no validated methods available to test androgenicity or antiandrogenicity in vitro. A problem with testing androgenicity using reporter genes is the possibility by other steroid receptors than androgen receptors to activate the same reporter gene, thereby lowering selectivity. To avoid this we have established a robust and very selective method, the AR CALUX reporter gene assay, to test androgenic and antiandrogenic activity of compounds in vitro. This assay uses a human U2-OS cell line stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 0 publications
4
44
0
Order By: Relevance
“…CALUX assays are used to identify receptor-mediated signaling pathways of gene expression by specific compounds such as estrogens and androgens (44,45). We relied on these bioassays to agnostically measure ER and GR agonist and antagonist activity profiles.…”
Section: Luciferase Assay Overviewmentioning
confidence: 99%
“…CALUX assays are used to identify receptor-mediated signaling pathways of gene expression by specific compounds such as estrogens and androgens (44,45). We relied on these bioassays to agnostically measure ER and GR agonist and antagonist activity profiles.…”
Section: Luciferase Assay Overviewmentioning
confidence: 99%
“…The AR CALUX bioassay is a reporter gene assay, comprising a human osteoblast cell line carrying a luciferase gene under transcriptional control of an androgen responsive element. The assay was performed according to published methods (Sonneveld et al, 2005;van der Burg et al, 2010), and androgen receptor activity responses were expressed as relative amounts of reference compounds equivalents; ng dihydrotestosterone (DHT) eq for agonist and lg flutamide (FLU) eq for antagonist activity expressed as per g of dry weight (dw) for sediment or g wet weight (ww) for clam samples. To measure antagonist activity, DHT (0.3 nM) was added to the culture medium.…”
Section: Ar-calux Assaymentioning
confidence: 99%
“…expected to go to ECVAM validation. Pre-validation study showed excellent agreement for 14 out of 16 chemicals (Van der Burg et al, 2010). Up to 85% agreement with rabbit test for 50 chemicals (Sonneveld et al, 2011). approaches to waive animal testing, such as exposure-based techniques.…”
Section: Ar Calux Reportermentioning
confidence: 83%